2015
DOI: 10.3109/10253890.2015.1079616
|View full text |Cite
|
Sign up to set email alerts
|

Hypercaloric diet modulates effects of chronic stress: a behavioral and biometric study on rats

Abstract: Obesity is a chronic disease that has been associated with chronic stress and hypercaloric diet (HD) consumption. Increased ingestion of food containing sugar and fat ingredients (comfort food) is proposed to "compensate" chronic stress effects. However, this eating habit may increase body fat depositions leading to obesity. This study evaluated behavioral/physiological parameters seeking to establish whether there is an association between the effects of HD intake and stress, and to test the hypothesis that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 55 publications
3
11
0
1
Order By: Relevance
“…We also observed reduced corticosterone levels in sickle mice with sickle diet and/or companionship. Since corticosterone is involved in stress response, this observation is consistent with reported stress-relieving effects of satisfying food 84 , 85 and social bonding 86 , 87 . Stress has been known for decades to enhance pain perception, especially in patients having chronic pain 88 91 .…”
Section: Discussionsupporting
confidence: 89%
“…We also observed reduced corticosterone levels in sickle mice with sickle diet and/or companionship. Since corticosterone is involved in stress response, this observation is consistent with reported stress-relieving effects of satisfying food 84 , 85 and social bonding 86 , 87 . Stress has been known for decades to enhance pain perception, especially in patients having chronic pain 88 91 .…”
Section: Discussionsupporting
confidence: 89%
“…ethological) circumstances, whereas the latter determines drug activity under stress-induced anxiety conditions. Although different types of stress trigger anxiety- and depression-like behaviours (Oliveira et al, 2015), the NSF method is designed to induce animal anxiety. Since the NSF test was conducted after an acute treatment, no depression should be developed in the animals (Harmer et al, 2017), ruling out the possibility that the observed different efficacy of PAM-2 is due to its antidepressant-like activity (Arias et al, 2015; Targowska-Duda et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Santos et al ( 2016 ) demonstrated that a high carbohydrate-containing diet administered for 12 weeks was anxiogenic and induced depressive symptoms after exposure to different stress paradigms. Chronic stress can also increase the consumption of food containing sugar and fat ingredients as a compensatory mechanism (comfort food) to reduce stress-related anxiety, which could lead to overeating and obesity long-term (Oliveira et al, 2015 ). In support of this hypothesis, other studies have shown that HFD administration to adult rats reduced anxiety (Leffa et al, 2015 ; McNeilly et al, 2015 ).…”
Section: Effects Of Obesity On Cognitive Functions and Moodmentioning
confidence: 99%